PENGARUH DANA MASYARAKAT TERHADAP PENYALURAN KREDIT PADA BANK UMUM DI SUMATERA SELATAN PERIODE 1994-2004 - Astariza Dian Maya Sari (Department of Development Economics, Universitas Sriwijaya, 2005)
This research is to know the form of relation between public funds(DPK) and credit distribution of Commercial Banks in South Sumatera. This paper also use the research period along 11 years. The data taken from many resources included the data from Badan Pusat Statisitk and Indonesian Bank. The result of regression research indicated that for period of 1994-2004. Kind of analysis that have been used is by using regression model. From the calculation the writer got R2 with the value 0,749 with indicated that 74,9 percent of credit. From the t-test and outher test we can conclude that public funds (DPK) are significant with the credit distribution. The more of distributions pubic funds (DPK) and credits in Commercial Banks is The Government Bank than Private National Banks. KeywordS: Public Funds, Commercial Banks, Credit Distributions